The Impact Of Regional Original Revenue, General Allocation Fund, And Revenue Sharing Fund On Regional Expenditure In Regency/City In Central Java Province (2018-2022) - Halimah, Putri; Chaniago, Sheren Rahmawati; Mustaruddin, Mustaruddin; Wendy, Wendy (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
This study aims to analyze the effect of Regional Original Revenue (PAD), General Allocation Fund (DAU), and Revenue Sharing Fund (DBH) on regional expenditure in districts and cities in Central Java Province in the period 2018-2022. Panel data was analyzed using descriptive statistical methods, Chow test, Hausman test, and panel data regression. The results showed that PAD, DAU and DBH had a positive and significant influence on regional expenditure. This finding indicates that regional fiscal independence and general allocations from the central government play an important role in determining the amount of regional expenditure. This study also highlights the importance of optimal PAD management as the main source of revenue to reduce dependence on transfer funds. The implication of this study is the need for local governments to improve efficiency in financial management and optimize the potential of PAD through appropriate policies. This research is expected to provide an in-depth understanding of how PAD, DAU, and DBH affect regional expenditure allocations, as well as provide policy recommendations for more efficient and effective regional financial management. This research is expected to contribute to increasing fiscal independence and accelerating sustainable development in Central Java Province.